Integration of Biorecognition Elements on PEDOT Platforms through Supramolecular Interactions. Issue 17 (10th July 2017) - Sappia, Luciano D.; Piccinini, Esteban; Marmisollé, Waldemar; Santilli, Natalia; Maza, Eliana; Moya, Sergio; Battaglini, Fernando; Madrid, Rossana E.; Azzaroni, Omar
Abstract : The rapidly emerging field of organic bioelectronics exploits the functional versatility of conducting polymers to transduce biological recognition events into electronic signals. For the majority of biosensors or biomedical devices, immobilization of a biorecognition element is a critical step to improve the biotic/abiotic interface. In this work, a simple strategy is described to construct large‐area all‐plastic poly(3, 4‐ethylenedioxythiophene) (PEDOT) electrodes displaying carbohydrate biorecognizable motifs. First, the method involves the preparation of PEDOT‐poly(allylamine) composites through supramolecular interactions. It is demonstrated by Raman and X‐ray spectroscopy and cyclic voltammetry that the PEDOT:poly(allylamine) ratio and the film electoactivity can be easily controlled. Then, carbohydrate motifs are covalently anchored to the primary amine groups by a straightforward route using divinylsulfone chemistry. The recognition‐driven assembly of the lectin concanavalin A (Con A) and the glycoenzyme glucose oxidase (GOx) onto mannosylated surfaces is demonstrated by surface plasmon resonance spectroscopy. Furthermore, the bioelectrocatalytic glucose detection mediated by the assembled enzyme is studied for all‐plastic and gold electrodes. Interestingly, the synergistic combination of conducting polymers and recognition‐directed assembly leads to a 2.7‐fold enhancement of the bioelectrocatalitic signal. Finally, it is proved that Con A/GOx nanoarchitectures can be constructed onto PEDOT platforms using the layer‐by‐layer technique. Abstract : Biorecognizable carbohydrate motifs are integrated onto poly(3, 4‐ethylenedioxythiophene) (PEDOT) films through the preparation poly(allylamine)–PEDOT composites via supramolecular interactions. The proposed strategy facilitates the straightforward supramolecular construction of versatile all‐plastic bioelectrochemical platforms. The bioelectrocatalytic detection of glucose is studied. Results reveal that the use of supramolecular PEDOT platforms leads to an enhancement of the bioelectrocatalytic signal.